Harpadas lenguas o la primera aparición de la Virgen de Guadalupe. Sobre el gongorismo de Francisco de Castro - Stein, Tadeo Pablo (El Colegio de México, 2014)
This article focuses on a passage of the Guadalupan poem La octavamaravilla y sin segundo milagro (c. 1680) by Francisco de Castro. Itstudies the gongorism proceeds of the mythological allusion and theperiphrasis. This paper proposes Castro’s passage as an example ofcreative imitation.